Autochthonous Dissolved Organic Matter Drives Bacterial Community Composition during a Bloom of Filamentous Cyanobacteria - Hoikkala, Laura; Tammert, Helen; Lignell, Risto; Eronen-Rasimus, Eeva; Spilling, Kristian; Kisand, Veljo (Frontiers in Marine Science, 2016)
The dynamics of dissolved organic matter (DOM) and the succession of bacterial community composition (BCC) were investigated during bloom of filamentous cyanobacteria in a mesocosm experiment conducted in the western Gulf of Finland, the Baltic Sea. The effects of labile dissolved organic carbon (glucose), inorganic nutrients (N and P) and large zooplankton (> 100 µm) on the DOM pool, bacterial production and the composition of bacterial communities were analysed over a period of ten days. In addition, the bioavailability of dissolved organic carbon (DOC) and its turnover by heterotrophic bacteria (biomass and respiration) were investigated in three one-week bacterial bioassays. Heterotrophic bacteria rapidly utilised about 25-55 % of the DOC released from the plankton community, thus assuming it to be highly labile DOC. More than half of the accumulating net DOC pool was degraded over seven days, thus assuming it to be labile. In average, labile autochthonous DOC was degraded with bacterial growth efficiency of 25%. A distinct succession of bacterial communities accompanied the supply of autochthonous DOM, with the most prominent responses occurring in a few single phylotypes of the Delta- and Gammaproteobacterial classes. About 40% of the variation in the relative shares of dominant bacterial classes could be explained by changes in the functional groups of autotrophs. Inorganic nutrient treatment proved beneficial to Deltaproteobacteria and increased bacterial production over that of other mesocosms.